Mineral Content of Various Portuguese Breads: Characterization, Dietary Intake, and Discriminant Analysis - Torrinha, Álvaro (2020)
The chemical composition and daily mineral intake (DMI) of six macro (calcium, magnesium, sodium, potassium, phosphorous, and chloride) and four microminerals (copper, iron, manganese, and zinc) were determined in four types of Portuguese breads (white wheat, maize, wheat/maize, and maize/rye breads). Samples were processed with microwave assisted digestion and mineral composition was determined with a high-resolution continuum-source atomic absorption spectrometer with flame and graphite furnace. Bread contributes to an equilibrated diet since it is rich in several minerals (0.21 mg/100 g of copper in wheat bread to 537 mg/100 g of sodium in maize/rye bread). Maize/rye bread presented the highest content of all minerals (except phosphorous and chloride), while the lowest levels were mainly found in wheat bread. Median sodium concentrations (422-537 mg/100 g) represented more than 28% of the recommended daily allowance, being in close range of the maximum Portuguese limit (550 mg/100 g). Maize/rye bread exhibited the highest DMI of manganese (181%), sodium (36%), magnesium (32%), copper (32%), zinc (24%), iron (22%), potassium (20%), and calcium (3.0%). A Principal Component Analysis (PCA) model based on the mineral content allowed the differentiation among white wheat, maize, and maize/rye bread. Zinc, magnesium, manganese, iron, phosphorus, potassium, copper, and calcium proved to be good chemical markers to differentiate bread compositions.